Dural Arteriovenous Fistulas in the Cavernous Sinus: Clinical Research and Treatment. (2nd August 2011) - Kurata, Akira; Suzuki, Sachio; Iwamoto, Kazuhisa; Nakahara, Kuniaki; Sasaki, Makoto; Kijima, Chihiro; Inukai, Madoka; Abe, Katsutoshi; Niki, Jun; Satou, Kimitoshi; Fujii, Kiyotaka; Kan, Shinichi
Abstract : Introduction . The purpose of this paper is to clarify the clinical course, with the dural carotid cavernous fistula (CCF), featuring a pallet of symptoms, paying special attention to radiological findings. Methods . Seventy-six consecutive patients with dural CCFs were investigated in detail, all of whom were defined by angiography. Results . The most common initial symptom was diplopia in 47 patients (62%) and the most frequently observed on arrival were type II, featuring cranial nerve palsies followed by the classical triad in 27, and then type I only with cranial nerve palsies. The time until admission with type I (mean: 6.7 W ± 6.0 ) was significantly shorter than that with type II (mean: 25.1 W ± 23.5 ). Branches from bilateral carotid arteries widely inflowing into bilateral carotid cavernous sinus were present in 30 (39%), 20 (26%) of which also demonstrated direct inflow into the intercavernous sinus. type I and II had more multiple venous drainage routes as compared with type III (classical triad only on arrival) and IV (initial development of the classical triad followed by cranial nerve palsy). Conclusion . In our series of dural CCF patients, the most common initial symptom was cranial nerve palsy, mostly featuring multiple venous drainage including cortical drainage. Such palsies should be added to the classical triad as indicative symptoms. Bilateral carotid arteries often inflow into cavernous and intercavernous sinuses, which should be taken into account in choice of therapeutic strategy.